Comparative Analysis of Halal Policy Implementation and Regulation: A Case Study of Indonesia and Japan in the Context of the Global Market - Rani Apriani; Tidar Bayu Herlambang (Universitas Muhammadiyah Purwokerto, 2026)
Halal certification standards are a form of assurance that every product to be used or consumed meets Islamic sharia criteria. Currently, several countries with minority Muslim populations are striving to establish halal assurance standards for products in circulation. This effort is a response to global market demands and the increasing awareness of Muslim consumers in those countries. Law Number 8 of 1999 concerning Consumer Protection prohibits businesses from producing and/or trading goods or services that do not comply with halal production requirements. This study aims to analyze the comparative regulatory framework and implementation of halal product assurance policies in Indonesia and Japan, as well as their implications for the global market. Indonesia enacted Law Number 33 of 2014 concerning Halal Product Assurance, which is mandatory and oriented towards protecting domestic Muslim consumers. This is reinforced by Government Regulation Number 42 of 2024 concerning the Implementation of the Halal Product Assurance Sector, with the Halal Product Assurance Organizing Agency as the central authority. In contrast, Japan adopts a voluntary (market-driven) approach, focused on facilitating tourism and exports by involving various private certification bodies. Using descriptive qualitative methods and regulatory document analysis, the study's key findings demonstrate fundamental differences in policy paradigms: Indonesia employs a centralized, mandatory model, while Japan employs a decentralized, facilitation model. These differences impact competitiveness and international recognition. It concludes that Indonesia needs to improve bureaucratic efficiency, while Japan needs to strengthen the harmonization of its standards for the global market.